Crizotinib vs platinum‐based chemotherapy as first‐line treatment for advanced non‐small cell lung cancer with different ROS1 fusion variants. (13th March 2020) - Xu, Haiyan; Zhang, Quan; Liang, Li; Li, Junling; Liu, Zhefeng; Li, Weihua; Yang, Lu; Yang, Guangjian; Xu, Fei; Ying, Jianming; Zhang, Shucai; Wang, Yan
Abstract: Background: ROS1 gene fusion represents a specific subtype of non‐small cell lung cancer (NSCLC). Crizotinib is recommended for ROS1‐ positive NSCLC due to its favorable outcome in published clinical trials. However, due to the low incidence of ROS1‐ positive NSCLC, there is limited information on real‐world clinical outcomes in patients treated with either crizotinib or platinum‐based doublet chemotherapy. Methods: Outcomes were recorded in 102 patients with stage Ⅲb or Ⅳ NSCLC who were treated at four Chinese hospitals between April, 2010 and June, 2019. Results: Of the 102 patients followed, 71.6% were females, 81.4% were non‐smokers, and 98.0% had adenocarcinoma. First‐line treatment with crizotinib achieved a significantly longer median progression‐free survival (PFS) compared with platinum‐based chemotherapy (14.9 months vs 8.5 months, respectively; P  < .001). Next‐generation sequencing (NGS) identified 61 patients who had ROS1 fusion variants, including CD74 (n = 33) and non‐CD74 (n = 28) variants. In patients harboring CD74 fusion variants, the median PFS with first‐line crizotinib treatment was significantly longer than in those harboring non‐CD74 fusion variants (20.1 months vs 12.0 months, respectively; P  = .046). However, in patients treated with platinum‐based chemotherapy, there was no significant difference in PFS between the CD74 and non‐CD74 variant groups (8.6 months vs 4.3 months, respectively; P  = .115). Overall survival (OS) was not reached. Conclusions: First‐line therapy with crizotinib is more beneficial than platinum‐based chemotherapy in patients with advanced NSCLC with different ROS1 fusion variants. Patients harboring CD74 fusion variants appear to respond better to crizotinib. Abstract : For first‐line treatment in advanced NSCLC with ROS1 rearrangement, crizotinib is more beneficial than platinum‐based chemotherapy. Patients harboring ROS1 CD74 fusion variants who are treated with first‐line crizotinib therapy have better PFS than those harboring non‐CD74 fusion variants. With first‐line platinum‐based chemotherapy, patients in both the CD74 and non‐CD74 fusion variant groups demonstrated a short PFS with no significant difference observed.